An Overview of International Staff Time Measurement Validation Studies of the RUG-III Case-mix System - Luke A Turcotte; Jeff Poss; Brant Fries; John P Hirdes (SAGE Publishing, 2019)
The RUG-III case-mix system is a method of grouping patients in long-term and post-acute care settings. RUG-III groups patients by relative per diem resource consumption and may be used as the basis for prospective payment systems to ensure that facility reimbursement is commensurate with patient acuity. Since RUG-III's development in 1994, more than a dozen international staff time measurement studies have been published to evaluate the utility of the case-mix system in a variety of diverse health care environments around the world. This overview of the literature summarizes the results of these RUG-III validation studies and compares the performance of the algorithm across countries, patient populations, and health care environments. Limitations of the RUG-III validation literature are discussed for the benefit of health system administrators who are considering implementing RUG-III and next-generation resource utilization group case-mix systems.